Using the Problem-Antecedent-Consequences-Solution Curriculum to Improve Socio-Sexual Decision-Making of Students on the Autism Spectrum - Wolfe, Pamela S.; Karal, Muhammed A.; Taylor, Jonte' C. (Journal of the American Academy of Special Education Professionals, 2024)
Sexuality education is an essential part of a comprehensive curriculum for individuals with disabilities as emerging adults. Lack of socio-sexuality education for individuals with disabilities has been linked to limited resources and training for teachers/personnel, and restrictive attitudes. The present study examined the effectiveness of the Problem-Antecedent-Consequences-Solution (PACS) curriculum to teach socio-sexuality skills for a group of adolescent students on the autism spectrum. Results indicated that four areas of flirting, using the stall, entering the bathroom, and passing gas resulted in significant differences for the participants. The curriculum showed promise for permitting adolescent students on the spectrum access to important socio-sexuality information that might promote self-advocacy skills and protection from abuse.